Analisis Volume Satuan Sepeda Motor pada Pagi & Sore Hari ke Jl. Dahlia dari Arah Alun-alun Menggunakan Aplikasi SPSS - Amri Gunasti; Rafi Ramadhan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the difference in the volume of motorcycle traffic in the morning and evening on Jalan Dahlia which leads from the Square. The data was collected through direct observation methods during a specific period during morning and evening rush hours, then analyzed to determine vehicle flow patterns, traffic density levels, and significant differences between the two time periods. In addition, this study also considers supporting factors such as community activities, working hours, and daily travel patterns of road users that affect traffic intensity. The results of the study showed that there was a significant difference in vehicle volume, where the volume of motorcycles in the morning tended to be higher than in the afternoon due to the dominance of trips to work and school. On the other hand, in the afternoon the traffic volume is relatively more spread due to variations in the return time of road users. These findings are expected to be a reference for related parties, especially local governments and transportation agencies, in traffic management planning, transportation operational timing, and efforts to improve the safety and comfort of road users in the area.